DEHYDROGENATIVE POLYMERIZATION OF NEW ALKYLSILANES CATALYZED BY CP(2)MCL(2)/RED-AL SYSTEM (M=TI, HF) - WOO, HG; KIM, SY; CHO, EJ; JUNG, IN (KOREAN CHEMICAL SOC, 1995)
Substituted 3-phenyl-1-silabutanes, 3-chlorophenyl-1-silabutane (1), 3-tolyl-1-silabutane (2), and 3-phenoxyphenyl-1-silabutane (3), were prepared in 68-98% yield by reduction of the corresponding substituted 3-phenyl-1,1-dichloro-1-silabutanes with LiAlH4. The dehydrogenative homopolymerization and copolymerization of the silanes were performed with Cp(2)MCl(2)/Red-Al (M=Ti, Hf) catalyst system. The molecular weights of the resulting polymers were in the range of 600 to 1100 (vs polystyrene) with degree of polymerization (DP) of 5 to 8 and polydispersity index (PDI) of 1.6 to 3.8. The monomer silanes underwent the dehydrogenative polymerization with Cp(2)TiCl(2)/Red-Al catalyst to produce somewhat higher molecular weight polysilanes compared with Cp(2)HfCl(2)/Red-Al catalyst.
Keywords: BOND METATHESIS MECHANISM; POLYSILANE HIGH POLYMERS; PRIMARY ORGANOSILANES; COMPLEXES; SILANES; DEHYDROPOLYMERIZATION; PHENYLSILANE; ZIRCONOCENE